2007
DOI: 10.1021/je600593c
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium and Partition of Iodide in an Aqueous Biphasic System Formed by (NH4)2SO4 + PEG + H2O at 25 °C

Abstract: The partitioning of iodide was studied in an aqueous biphasic system (ABS) comprised of ammonium sulfate, polyethylene glycol (PEG), and water at 25 °C. The average molecular weights of PEG were (2078, 3819, and 9887) g·mol-1. In a prior determination, data for the liquid−liquid equilibrium of this system were obtained and correlated with the nonrandom, two-liquid (NRTL) thermodynamic model. Data on the partition coefficients and percentage extraction of iodide were obtained , which were correlated as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Figure A1. Experimental LLE tie-line data for the aqueous PEG10000-AS system at 298.15 K by Graber et al (2007), shown as the mole fraction of water (x(water)) in the ternary PEG10000-AS-water liquid bulk mixture vs. the mole fraction of AS (x (electrolyte)) of the PEG10000-AS mixture on a water-free basis. The dashed blue line indicates the dry PEG10000 : AS mass ratio of 2 : 1 studied in the DASH-SP experiments.…”
Section: Data Availabilitymentioning
confidence: 99%
“…Figure A1. Experimental LLE tie-line data for the aqueous PEG10000-AS system at 298.15 K by Graber et al (2007), shown as the mole fraction of water (x(water)) in the ternary PEG10000-AS-water liquid bulk mixture vs. the mole fraction of AS (x (electrolyte)) of the PEG10000-AS mixture on a water-free basis. The dashed blue line indicates the dry PEG10000 : AS mass ratio of 2 : 1 studied in the DASH-SP experiments.…”
Section: Data Availabilitymentioning
confidence: 99%
“…Particularly, ATPS formed by PEG + (NH 4 ) 2 SO 4 + H 2 O has been studied for a long time [14,15]. These ATPS have been used in the extraction of various analytes, such as ionic species [16,17], small molecules [18], and also in the partition proteins [19]. These ATPS in general, have physicochemical properties which vary considerably with molecular weight PEG.…”
Section: Introductionmentioning
confidence: 99%
“…Iodine is an important ingredient in the generation of thyroid hormones, which regulates several biochemical reactions associated with growth and developments of reproductive systems, immune defense systems and many more biological processes. 18,20 However, use of the phase forming component of ABS itself in speciation is still unexplored. [15][16][17] Different iodine species are responsible for their varied applications.…”
Section: Introductionmentioning
confidence: 99%